Approximation of Generalized Compound Ray leigh Distribution Parameters Through Bayesian with General Entropy - Srivastava, Prof. Uma; Yadav, Parul; Singh, Satya Prakash (International Journal of Psychosocial Rehabilitation, 2019)
This paper considers the Bayes estimate of Location parameter α of three parameter Generalized Compound Rayleigh distribution with a chaotic loss known as General Entropy loss function (GELF). The Lindley approximation is applied to obtain the Approximate Bayes estimate of Location parameter of Generalized Compound Rayleigh distribution under the GELF. The obtained results are compared through R-programming.